OPTIMIZATION OF “PAS COFFEE ROASTERY” WORK ACTIVITIES USING THE TOTAL QUALITY MANAGEMENT (TQM) CONCEPT AT CLASS IIA METRO PRISON - Nasyt, Muhammad Farhan; Indahdewi, Lauditta (Universitas Nusa Cendana, 2025)
The research conducted to discuss the optimization of work activities at